2014
DOI: 10.1186/1756-0500-7-738
|View full text |Cite
|
Sign up to set email alerts
|

Acute elevation of intra-abdominal pressure contributes to extravascular shift of fluid and proteins in an experimental porcine model

Abstract: BackgroundIntra-abdominal hypertension and abdominal compartment syndrome contribute significantly to increased morbidity and mortality in critically ill patients. This study describes pathophysiologic effects of the acutely elevated intra-abdominal pressure on microvascular fluid exchange and microcirculation. The resulting changes could contribute to development of organ dysfunction or failure.Methods16 pigs were randomly allocated to a control-group (C-group) or an interventional group (P-group). After 60 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…There is increasing evidence that fluid infusion affects postoperative outcomes, and plays a crucial role in critically ill patients. 8,9,13,14 Excessive perioperative fluid loading leads to extravascular fluid accumulation and weight gain, which corresponds with increased mortality and morbidity during the early postoperative period. 6,8,15 Several meta-analyses have reported that goaloriented fluid therapy significantly reduces renal and pulmonary postoperative complications, and accelerates the first bowel movement, the resumption of normal diet, and shortens the length of stay in hospital.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is increasing evidence that fluid infusion affects postoperative outcomes, and plays a crucial role in critically ill patients. 8,9,13,14 Excessive perioperative fluid loading leads to extravascular fluid accumulation and weight gain, which corresponds with increased mortality and morbidity during the early postoperative period. 6,8,15 Several meta-analyses have reported that goaloriented fluid therapy significantly reduces renal and pulmonary postoperative complications, and accelerates the first bowel movement, the resumption of normal diet, and shortens the length of stay in hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a growing data set presents an increase in IAP following inflammatory-related intestine edema. 9,24,25 Surgery-related injury induces the release of proinflam- matory cytokines, such as tumor necrosis factor α (TNFα), vascular endothelial growth factor (VEGF), many interleukins, histamine, and E-selectine, which may disturb vascular permeability, and increase fluid shift into the extravascular space. 26,27 Moreover, surgery-related perioperative stress induces the release of antidiuretic hormone, cortisol and corticotrophins, and stimulates the renin-angiotensin-aldosterone system to increase salt and fluid retention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…no linear relationship negligible correlation with irrelevant relationship low correlation, definite but small relationship moderate correlation with significant relationship high correlation with strong relationship very high correlation with strong dependable relationship [8,10,11,[14][15][16]. ACS definition in an animal model can be stated if an artificially increased IAP leads to circulatory, renal, respiratory insufficiency [9].…”
Section: Methodsmentioning
confidence: 99%